Equacionamento das crises bancárias pós-1980: atuação dos Bancos Centrais e dos Tesouros em casos selecionados e comparação com o período 2007-2009 - Amora, Paulo Roberto Piccina (2013)
This paper discusses some ideas and different opinions about recent systemic banking crises. The study builds a broad framework of this episodes pointing issues like the nature of banking crises; the actions and the economic policies put in place by governments to promote the settlement of the banking crises of Chile (in the 1980s) and Japan (in the 1990s); the pragmatic and static point of view of the International Monetary Fund about the recent banking crises